2019
DOI: 10.1039/c8nr10235j
|View full text |Cite
|
Sign up to set email alerts
|

To heat or not to heat: a study of the performances of iron carbide nanoparticles in magnetic heating

Abstract: Heating magnetic nanoparticles with high frequency magnetic fields is a topic of interest for biological applications (magnetic hyperthermia) as well as for heterogeneous catalysis. This study shows why FeC NPs of similar structures and static magnetic properties display radically different heating power (SAR from 0 to 2 kW.g -1 ). By combining results from Transmission Electron Microscopy (TEM), Dynamic Light Scattering (DLS) and static and time-dependent high-frequency magnetic measurements, we propose a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 50 publications
3
63
0
Order By: Relevance
“…When comparing structural characterization of 1 and 2 (Figure a,b), no significant differences were observed neither in the XRD patterns nor in the static magnetic properties measured by VSM at 300 K (see also the Supporting Information, Figure S10 for VSM at 5 K). However, the SAR of the NPs 2 dropped from 600 to 350 W g −1 after Ni enrichment (Figure c), as expected after the addition of a softer material such as Ni …”
Section: Figuresupporting
confidence: 74%
See 1 more Smart Citation
“…When comparing structural characterization of 1 and 2 (Figure a,b), no significant differences were observed neither in the XRD patterns nor in the static magnetic properties measured by VSM at 300 K (see also the Supporting Information, Figure S10 for VSM at 5 K). However, the SAR of the NPs 2 dropped from 600 to 350 W g −1 after Ni enrichment (Figure c), as expected after the addition of a softer material such as Ni …”
Section: Figuresupporting
confidence: 74%
“…However, the SAR of the NPs 2 dropped from 600 to 350 W g À1 after Ni enrichment (Figure 1 c), as expected after the addition of a softer material such as Ni. [39] NPs 2 were supported on SiRAlOx (Supporting Information, Figure S11) and evaluated for CO 2 hydrogenation. As expected, 2/SiRAlOx displayed a slightly higher amount of Ni by ICP-MS than NPs 1/SiRAlOx (6.1 wt % vs. 5.6 wt % respectively), but a comparable Fe content (2.0 wt % vs. 1.8 wt %).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…It has been reported that the heating threshold for FeC-NPs corresponds to an amplitude of 30 mT and that these NPs display a remarkably high heating capability at 48 mT (up to 2000 W/g). 25 On the other hand, Fe-NPs start heating at higher amplitudes (>35mT) and reach 820 W/g at 48 mT, while alloying Fe with At the opposite, low anisotropy NPs such as the Fe 0.5 Co 0.5 display a SAR starting to increase at low field and their SAR(µ 0 H) has a higher slope. If these MNPs were measured at very high field, the high-anisotropy NPs would have a much larger SAR than the low-anisotropy ones.…”
Section: Magnetic and Heating Properties Of The Heating Agentsmentioning
confidence: 99%
“…In this case, experiments would conclude to a local heating even though there is none. With respect to ii), it is a well-known fact that, in liquid phase, MNPs excited by an external magnetic field form chains, which are sometimes several tens or hundreds of microns wide, depending on the MNP properties, their functionalization, the magnetic field amplitude, and so forth 39,40,41,42 . When such chains form, the measured "local" temperature is not the temperature at the surface of an isolated nanoscale object, but the temperature at the surface and/or inside a micron-scale magnetically heated assembly of MNPs.…”
Section: The Evolution Of the Diffraction Pattern In The Temperature mentioning
confidence: 99%